2015
DOI: 10.1016/j.cub.2015.01.057
|View full text |Cite
|
Sign up to set email alerts
|

Taste Quality Decoding Parallels Taste Sensations

Abstract: In most species, the sense of taste is key in the distinction of potentially nutritious and harmful food constituents and thereby in the acceptance (or rejection) of food. Taste quality is encoded by specialized receptors on the tongue, which detect chemicals corresponding to each of the basic tastes (sweet, salty, sour, bitter, and savory [1]), before taste quality information is transmitted via segregated neuronal fibers [2], distributed coding across neuronal fibers [3], or dynamic firing patterns [4] to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
88
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(98 citation statements)
references
References 41 publications
10
88
0
Order By: Relevance
“…For all of the time windows, we determined the significance by both a two-tailed t -test and a group-level permutation test (see Methods). For multiple comparison corrections, a time-cluster-based approach was applied in which a cluster of time points was significant after the correction only when it had more than five consecutively significant time points23 (see Supplementary Methods: Time-cluster-based approach for multiple comparison correction). The rows of red dots and green horizontal lines below each panel in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For all of the time windows, we determined the significance by both a two-tailed t -test and a group-level permutation test (see Methods). For multiple comparison corrections, a time-cluster-based approach was applied in which a cluster of time points was significant after the correction only when it had more than five consecutively significant time points23 (see Supplementary Methods: Time-cluster-based approach for multiple comparison correction). The rows of red dots and green horizontal lines below each panel in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In another study, Douglas et al [25] stated that EEG data can outperform fMRI data in decoding the belief decision. Moreover, decoding the taste categories was recently performed by Crouzet et al [26] using EEG. The above mentioned studies suggest the potential of EEG for decoding brain activity.…”
Section: Introductionmentioning
confidence: 99%
“…This restriction may be overcome in the future with better machine for the collection of data. In case of EEG, this research area is still progressing and only few studies have been reported in past years [24, 26] which shows lack of research in this area. The same is stated by Agrawal et al, in an article “EEG and NIRS offer portable solutions but with their signal quality no substantial results for predicting brain activity have been reported” [49].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations